The Arabidopsis MIEL1 E3 ligase negatively regulates ABA signalling by promoting protein turnover of MYB96 - Lee, Hong Gil (Nat Commun, 2016)
The phytohormone abscisic acid (ABA) regulates plant responses to various environmental challenges. Controlled protein turnover is an important component of ABA signalling. Here we show that the RING-type E3 ligase MYB30-INTERACTING E3 LIGASE 1 (MIEL1) regulates ABA sensitivity by promoting MYB96 turnover in Arabidopsis. Germination of MIEL1-deficient mutant seeds is hypersensitive to ABA, whereas MIEL1-overexpressing transgenic seeds are less sensitive. MIEL1 can interact with MYB96, a regulator of ABA signalling, and stimulate its ubiquitination and degradation. Genetic analysis shows that MYB96 is epistatic to MIEL1 in the control of ABA sensitivity in seeds. While MIEL1 acts primarily via MYB96 in seed germination, MIEL1 regulates protein turnover of both MYB96 and MYB30 in vegetative tissues. We find that ABA regulates the expression of MYB30-responsive genes during pathogen infection and this regulation is partly dependent on MIEL1. These results suggest that MIEL1 may facilitate crosstalk between ABA and biotic stress signalling.